The Neutrophil to Lymphocyte Ratio Is Associated With the Risk of Subsequent Dementia in the Framingham Heart Study - Ramos-Cejudo, Jaime; Johnson, Andrew D.; Beiser, Alexa; Seshadri, Sudha; Salinas, Joel; Berger, Jeffrey S.; Fillmore, Nathanael R.; Do, Nhan; Zheng, Chunlei; Kovbasyuk, Zanetta; Ardekani, Babak A.; Bubu, Omonigho M.; et al. (Frontiers in Aging Neuroscience, 2021)
Objective: Active neutrophils are important contributors to Alzheimer’s disease pathology through the formation of capillary stalls that compromise cerebral blood flow and through aberrant neutrophil signaling that advances disease progression. The neutrophil to lymphocyte ratio (NLR) is a proxy of neutrophil-mediated inflammation and higher NLR is found in persons diagnosed with clinical Alzheimer’s disease. The objective of this study was to investigate whether increased NLR in older adults is independently associated with risk of subsequent dementia. Methods: We examined associations of baseline NLR with incident dementia risk in the community‐based Framingham Heart Study longitudinal cohorts. The association between NLR and risk of dementia was evaluated using the cumulative incidence function and inverse probability weighted Cox proportional cause-specific hazards regression models, with adjustment for age, sex, BMI, systolic and diastolic blood pressure, diabetes, current smoking status, LDH, LDL, total cholesterol, triglycerides, and history of CVD. Random forest survival models were used to evaluate the relative predictive value of the model covariates on dementia risk. Results: The final study sample included 1,648 FHS participants (average age, 69 years; 56% women). During follow‐up (median, 5.9 years), we observed 51 cases of incident dementia, of which 41 were Alzheimer’s disease cases. Results from weighted models suggested that the NLR was independently associated with incident dementia, and it was preceded in predictive value only by age, history of cardiovascular disease, and blood pressure at baseline. Conclusions: Our study shows individuals with higher NLR are at a greater risk of subsequent dementia during a 5.9‐year follow‐up period. Further evaluating the role of neutrophil-mediated inflammation in Alzheimer’s disease progression may be warranted.